Economy 4.0 - digitalisation and its effect on wage inequality - Mönnig, Anke [Verfasser]; Maier, Tobias [Verfasser]; Zika, Gerd [Verfasser] (My University, 2019)
"This paper contributes to the discussion of the impact of digital transformation on labour markets by analysing the impact on wage inequality. The novelty of this paper is on the one hand the quantitative approach that applies a macroeconometric input-output model which accounts for circular flow in the economy and feedback loops. Most of the studies on wage inequality and digital transformation focus on ex-post analysis. The applied quantitative model used in this paper also allows to perform ex-ante analysis. This is important, as economy 4.0 is not yet reflected in current datasets which makes statements about the impact of economy 4.0 on wage inequality on basis of ex-post analysis difficult. On the other hand, it uses the inequality measures S80/S20 that has been applied to a unique dataset on employment and wages. The dataset differentiates on industry and occupational level. That allows to identify industry-occupation combination and their location in the upper and/or lower 20 % share ratio of wage distribution. The analysis demonstrates that digital transformation increases wage inequality, however to a low extent. The increase in wage inequality is already implemented in the reference scenario due to structural and demographic change. Digital transformation strengthens the impact of structural change on wage inequality. Especially in the long run, wage inequality rises stronger than in the reference scenario. Because the digital transformation scenario does not confirm the polarization hypothesis, the impact of economy 4.0 on wage inequality remains rather low. The increasing demand of high-skilled employees is reflected in an increase in wage inequality. However, the relatively low impact of digitalisation on low-skilled employees prevents a stronger increase in wage inequality." (Authors' abstract, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.2.4 Wirtschaftszweige; G 2.1.1 Ökonomie / Märkte; T 3 Forschungsmethoden; Industrie 4.0; Digitalisierung; Lohnstruktur; Einkommensunterschied; Wirtschaftszweig; Bildungsniveau; Makroökonomie; Projektion; Szenario